Evaluation of the bioactive compounds and the antioxidant capacity of grape pomace. (23rd May 2014) - Iora, Sandra R. F.; Maciel, Giselle M.; Zielinski, Acácio A. F.; da Silva, Marcos V.; Pontes, Paula V. de A.; Haminiuk, Charles W. I.; Granato, Daniel
Summary Grape pomace is an agro‐industrial residue produced worldwide and mainly employed for animal feed or as a fertiliser. Several studies have shown that grape pomace is a rich source of bioactive compounds, such as phenolic compounds, polysaccharides, fatty acids and others. Three varieties of grape pomace were evaluated in this study. Antioxidant activity was determined by three different methods, namely, DPPH˙, ABTS and ferrous ion assays. Fatty acids and phenolic compounds were identified, respectively, by gas and liquid chromatography. Results showed that grape pomace is a rich source of polyunsaturated fatty acids and phenolic compounds. Cabernet Sauvignon pomace revealed higher values of total phenolic compounds, total flavonoids and total monomeric anthocyanin, and presented the lowest value of EC50, and thus a higher antioxidant activity among the samples analysed.